I Am a Warrior: An Analysis of the Military Masculine-Warrior Narrative Among U.S. Air Force Officer Candidates. Issue 1 (January 2021) - Do, James J.; Samuels, Steven M.
This qualitative study examines how cadets at the U.S. Air Force Academy make sense of their experiences, form attitudes and beliefs, construct identities, and how a vocal minority of men create and perpetuate a biased gender norm. Despite an institutional intention of egalitarianism, cadets construct a highly masculinized culture. Focus group and interview analyses show how cadets perpetuate the military masculine-warrior narrative in sensemaking and the construction of gender differences. We argue that the narratives become an acceptable way to express gender biases, overriding the actual reason for the existence of fitness testing. We conclude by addressing the contradiction between policies promoting the inclusion of women in the military and the sexism described above. Acknowledging the lived experience of military personnel would allow for better perceptions of gender equality and suggests potential directions for policy, practice, and future research.